2002
DOI: 10.1023/a:1014260513728
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: PLGA nanospheres should be more suitable for delivery to inflamed synovial tissue than microspheres due to their ability to penetrate the synovium. PLGA particulate systems with biocompatibility in the joint can provide local-therapy action in joint disease in a different manner depending on the size of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(38 citation statements)
references
References 15 publications
3
31
3
1
Order By: Relevance
“…30, 31,32 Large particles usually have an efficient depot effect for continuous antigen release. 31,33 We have proven that polyacrylate polymers conjugated to the E7 epitope formed microparticles (12-17 m), which were able to be efficiently taken up by APCs (including macrophages and dendritic cells), as well as to activate CD8 + and CD4 + cells to elicit adequate cellular immune responses against E7-expressing tumors. 14 However, it has been reported that very large-sized particles ranging from 50-100 m (which is larger than a typical APC) were least likely to be taken up by APCs, resulting in the generation of a low immune response.…”
Section: In Vivo Tumor Treatmentsmentioning
confidence: 99%
“…30, 31,32 Large particles usually have an efficient depot effect for continuous antigen release. 31,33 We have proven that polyacrylate polymers conjugated to the E7 epitope formed microparticles (12-17 m), which were able to be efficiently taken up by APCs (including macrophages and dendritic cells), as well as to activate CD8 + and CD4 + cells to elicit adequate cellular immune responses against E7-expressing tumors. 14 However, it has been reported that very large-sized particles ranging from 50-100 m (which is larger than a typical APC) were least likely to be taken up by APCs, resulting in the generation of a low immune response.…”
Section: In Vivo Tumor Treatmentsmentioning
confidence: 99%
“…As microscopias eletrônicas de varredura [56][57][58][59][60] (MEV) ou de transmissão 59,61,62 (MET) têm sido muito empregadas na obtenção de informações relativas à forma e ao tamanho das nanopartículas. A MET pode permitir também a diferenciação entre nanocápsulas e nanoesferas, possibilitando, inclusive, a determinação da espessura da parede das nanocápsulas 63,64 .…”
Section: Avaliação Morfológicaunclassified
“…However, the main limitation of drug administration into the joint cavity is the rapid clearance of drugs from the cavity after intra-articular administration. Therefore, controlled drug delivery systems (microspheres/microparticles) of intra-articular injection were extensively investigated in the past few years [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%